Autoantibodies binding to ubiquitin‐fold modifier‐conjugating enzyme 1 (Ufc1) and pleckstrin homology domain containing, family G (with RhoGef domain) member 2 (Plekhg2) are associated with mycobacterial infections. Issue 2 (12th September 2014) - Tellermann, A; Witte, T; Lansche, C; Stoll, M; Schmidt, RE; Baerlecken, NT
<x xml:space="preserve">Abstract</x> Objectives The diagnosis of extrapulmonary tuberculous infections and nontuberculous mycobacterial (NTM) infections is difficult because the symptoms are nonspecific and suitable specimens for bacterial culture are often not available. Recent publications reported the existence of autoantibodies in tuberculous infections. We screened for specific autoantibodies in mycobacterial infections. Methods We screened four in 29 patients with active mycobacterial infections and different controls using protein array technology. We could identify autoantibodies against ubiquitin‐fold modifier‐conjugating enzyme 1 (Ufc1) and pleckstrin homology domain containing, family G (with RhoGef domain) member 2 (Plekhg2) in all four patients. Subsequently, we designed enzyme‐linked immunosorbent assays (ELISAs) for the detection of autoantibodies binding to Ufc1 and Plekhg2. Results Autoantibodies binding to Ufc1 and Plekhg2 were found in 19 of 29 patients (66%) with active mycobacterial infections. In comparison, we found these autoantibodies in one of 31 patients (3%) with successfully treated mycobacterial infections, in three of 40 (8%) HIV‐infected patients not receiving combination antiretorviral therapy (cART) and in six of 134 (5%) blood donors. Interestingly, six of eight (75%) patients with HIV‐associated B‐cell non‐Hodgkin lymphoma (B‐NHL) at the onset of disease had autoantibodies against Ufc1 and Plekhg2, but none of nine (0%) patients after treatment of HIV‐associated B‐NHL, none of seven patients with non‐HIV‐associated B‐NHL and 11 of 115 (10%) patients with other malignant diseases had autoantibodies against both proteins. Conclusions In view of the high frequency of these autoantibodies, we postulate that they might be of potential use for additional diagnostics for mycobacterial infections, and further studies may shed light on the pathomechanisms of these two autoantibodies.